2011
DOI: 10.1016/j.bbr.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Repeated mirtazapine nullifies the maintenance of previously established methamphetamine-induced conditioned place preference in rats

Abstract: The atypical antidepressant mirtazapine enhances monoaminergic transmission; thus, mirtazapine therapy may counter the hypo-activation of monoamine systems associated with withdrawal from methamphetamine abuse. Human addiction therapy will likely require chronic administration that is given after brain and behavioral maladaptations are established. To emulate this scenario in rats, we ascertained if acute or repeated mirtazapine treatments could antagonize previously established consequences of repeated metham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…Mirtazapine shows preclinical promise in several models including motor sensitization (McDaid et al, 2007), conditioned place preference (Voigt and Napier, 2011;Herrold et al, 2009;Kang et al, 2008;Voigt et al, 2011;Graves et al, 2012), and models of drug-seeking in rats trained to self-administer (Graves and Napier, 2011). Testing mirtazapine in multiple paradigms strengthens confidence in interpreting outcomes; this serves as the basis of the following discussion.…”
Section: Mirtazapine: Pharmacology Physiology and Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Mirtazapine shows preclinical promise in several models including motor sensitization (McDaid et al, 2007), conditioned place preference (Voigt and Napier, 2011;Herrold et al, 2009;Kang et al, 2008;Voigt et al, 2011;Graves et al, 2012), and models of drug-seeking in rats trained to self-administer (Graves and Napier, 2011). Testing mirtazapine in multiple paradigms strengthens confidence in interpreting outcomes; this serves as the basis of the following discussion.…”
Section: Mirtazapine: Pharmacology Physiology and Behaviormentioning
confidence: 99%
“…We have tested the efficacy of mirtazapine at attenuating the expression of methamphetamine-induced CPP (Voigt and Napier, 2011;Herrold et al, 2008;Voigt et al, 2011). Interestingly, a 24hr pretreatment of mirtazapine is sufficient to attenuate the expression of methamphetamine-induced place preference using a single-pairing CPP paradigm (Herrold et al, 2008).…”
Section: Mirtazapine: Pharmacology Physiology and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Mirtazapine was administered intraperitoneally (ip) as 5.0mg/ml/kg. This dose was selected based on our extensive prior studies showing that it is sufficient to reduce several forms of methamphetamine- (Graves and Napier, 2011;Herrold et al, 2009;McDaid et al, 2007;Voigt et al, 2011;Voigt and Napier, 2011), and morphine- (Graves et al, 2012a) motivated behaviors in rats without increasing latency to lever press in cue reactivity paradigm or altering coordinated motor function on a rotarod (Graves and Napier, 2011). Ketanserin tartrate (Sigma-Aldrich, St. Louis, MO) was dissolved in sterile H 2 O and administered ip at doses of 1.0, 2.5, or 5.0mg/ml/kg (as the free base).…”
Section: Methodsmentioning
confidence: 99%
“…Mirtazapine is an atypical antidepressant with a complex pharmacological profile that includes antagonism at 5-HT 2A/2C receptors (De Boer, 1995;Wikstrom et al, 2002). Mirtazapine attenuates various behaviors motivated by abused drugs, including methamphetamine (Herrold et al, 2009;Voigt et al, 2011;Graves and Napier, 2011;Voigt and Napier, 2011) and morphine (Graves et al, 2012a) in rats, and reduces cocaine intake in humans (Graves et al, 2012b). We recently revealed that mirtazapine reduces the capacity of the dopamine D2/D3 receptor agonist, pramipexole, to induce risky decision-making by rats performing a probability discounting task (Holtz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%